Pengaruh Kompetensi, Independensi, Time Budget Pressure, Dan Pengalaman Kerja Terhadap Kualitas Audit Di Kantor Akuntan Publik (KAP) Wilayah Kota Medan - Jessen Yap, Farina (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2023)
The report from the auditor greatly affected the actions taken by the third parties who are using the auditor’s report. Therefore, Auditors must maintain the quality of their audit so that they do not mislead third parties in their decision making. There are several factors that can affect the quality of the audit, they are Competence, Independence, Time Budget Pressure, and Work Experience. The method used by writer is quantitative approach. The data resources used in this research is primary data (questionnaire). From 51 questionnaires that were shared, there were 12 qustionnaires that were not filled, so that only 39 questionnaires could be processed. The data analysis method used is multiple regression analysis using statistical test tools, Statistical Package for Social Sciences (SPSS) version 26. The results of this research showed that partially there was no effect between Competence on Audit Quality, there was an effect between Independence on Audit Quality, there was no effect between Time Budget Pressure on Audit Quality, there was no effect between Work Experience on Audit Quality. Simultaneously there was an effect of competence, independence, time budget pressure, work experience on audit quality